The usefulness of accounting information and management accounting practices under environmental uncertainty - Rui Pires; Maria do Céu Alves; Catarina Fernandes (Journal of Risk and Financial Management, 2023)
The purpose of this paper is twofold. Firstly, we aim to investigate the relationships among environmental uncertainty, broad-scope and timely management accounting information usefulness, and (traditional and contemporary) management accounting practices (MAPs) usage. Secondly, we intend to explore how these relationships influence decision-makers' satisfaction with management accounting information. Survey data were obtained through an online questionnaire from 114 large manufacturing companies operating in Portugal. The findings indicate a positive relationship between environmental uncertainty and timely management accounting information usefulness and between (broad-scope and timely) management accounting information usefulness and (traditional and contemporary) MAPs usage. The findings also show that decision-makers' satisfaction with management accounting information improves when there is a good fit between environmental uncertainty, broad-scope and timely management accounting information usefulness, and MAPs usage. In this way, organisations need to adjust the implementation and usage of MAPs to contextual factors, using both contemporary and traditional MAPs, to achieve greater decision-makers' satisfaction with management accounting information. Thus, the results achieved in this study are useful for both theory and practice and have several implications for professionals engaged in MAPs implementation and decision-making activities.
Keywords: 650; congruent fit; environmental uncertainty; management accounting information usefulness; management accounting practices (MAPs); online questionnaire survey; Portugal; satisfaction with management accounting information